The COVID-19 Isolation Unit Design at Railway-Line Informal Settlement with Participatory Planning Approach - Ariyanto, Yusuf; Wardhani, Dyah Kusuma; Kristi , Yulia (RUAS, 2023)
The increase in the number of patients who are positive for COVID-19 is not equipped by the capacity of isolation rooms in hospitals and safe houses assigned by the government, only 20% of infected patients require hospital care, while the rest 80% are suggested for self-quarantine and isolation. The problem becoming more complex for dense informal settlements, as a case study is a railway-line settlement in Surabaya. Based on the result of the observation, the house at the railway-line settlement has not met the healthy housing category, if there are residents infected with the COVID-19 virus, self-quarantine in their own house is also inadequate and it can cause the spread of the virus to other family members. This study aims to find a design solution for self-isolation units that can be applied in dense informal settlements during a pandemic. In addition to meeting health requirements, this isolation unit must be easy to assemble, cheap, and fast in its construction. The approach used for its design is participatory planning so that the design results are suitable for community needs and strengthen the community's sense of belonging towards its development and maintenance.